Characterisation of asphalt binder modified with ethylene–propylene–diene–monomer (EPDM) rubber waste from automobile industry. Issue 9 (2nd September 2021) - Kumar, Ankush; Choudhary, Rajan; Kumar, Abhinay
Abstract : Ethylene–propylene–diene–monomer (EPDM) is a high-quality synthetic rubber widely used in non-tyre automotive parts. Waste EPDM rubber is generated at several industries, manufacturing units, and automobile repair/service stations. The present study aims at the evaluation of asphalt binders and mixes with waste EPDM as a modifier. Modification was attempted with four EPDM contents (2%, 4%, 6% and 8% by binder weight). Storage stability was checked for the modified blends with and without a crosslinking agent (sulphur). Binder characterisation was done through penetration, softening point, temperature and frequency sweeps, master curve, multiple stress creep recovery, Burger's model fit, and binder yield energy tests. Performance of bituminous mixtures with EPDM-modified binders was also evaluated through Hamburg wheel tracking, stiffness modulus, and indirect tensile strength tests. The incorporation of EPDM enhanced the rutting and fatigue performance of the binder. Mixtures showed better stiffness, rutting resistance and tensile strength compared to those with control mixes.